Tapering for Marathon and Cardiac Autonomic Function - Hug, B.; Heyer, L.; Naef, N.; Buchheit, M.; Wehrlin, J. P.; Millet, G. P. (International Journal of Sports Medicine, 2014)
The purpose of this study was to investigate changes in post-exercise heart rate recovery (HRR) and heart rate variability (HRV) during an overload-tapering paradigm in marathon runners and examine their relationship with running performance. 9 male runners followed a training program composed of 3 weeks of overload followed by 3 weeks of tapering (−33±7%). Before and after overload and during tapering they performed an exhaustive running test (Tlim). At the end of this test, HRR variables (e.g. HRR during the first 60 s; HRR60 s) and vagal-related HRV indices (e.g. RMSSD5–10 min) were examined. Tlim did not change during the overload training phase (603±105 vs. 614±132 s; P=0.992), but increased (727±185 s; P=0.035) during the second week of tapering. Compared with overload, RMSSD5–10 min (7.6±3.3 vs. 8.6±2.9 ms; P=0.045) was reduced after the 2nd week of tapering. During tapering, the improvements in Tlim were negatively correlated with the change in HRR60 s (r=−0.84; P=0.005) but not RMSSD5–10 min (r=−0.21; P=0.59). A slower HRR during marathon tapering may be indicative of improved performance. In contrast, the monitoring of changes in HRV as measured in the present study (i.e. after exercise on a single day), may have little or no additive value.
Keywords: endurance performance; cardiac autonomic activity; heart rate recovery; heart rate variability; parasympathetic reactivation